Where's my future? - Levene, Sam; Milette, Jacques; Lore, Louise executive production (Ottawa : Canadian Broadcasting Corporation [production company] ; Kuala Lumpur : Visual Resources [distributor], 1995)
Generation X is the name given by the media to young adults in their twenties who face a difficult and uncertain economic future
Award winning films and videos
Camera, Don Spence...[et al.] ; sound, Ken Mackay...[et al.] ; music, Sloan
VHS format
Keywords: Youth -- Employment -- United States